The Effectiveness of Self-Control Technique in Reducing Bully Tendencies amongst Primary School Pupils in Edo State, Nigeria: Counselling Implication - Igbineweka, Martins Noyosase; Jesuorobo, Wellington Omosefe (Insight: Jurnal Ilmiah Psikologi, 2022)
Abstract This study investigated the effectiveness of Social-control technique (SCT) on reducing bullying tendencies among primary school pupils and sex difference in Edo state, Nigeria and suggested some implications for counselling. The design was the quasi-experimental research design. Three research questions and their corresponding hypotheses guided the study, while the population comprised of four thousand four hundred and sixty seven (44 67) 2020/2021Basic (5) pupils in primary schools in Egor Local Government Area, Edo State. The instrument used for the study was a questionnaire titled “Olweus Bully/Victims Questionnaire’’ (OBVQ) and modified by the researchers. Data collected were analysed using paired t-test and Fisher Z-test and independent samples statistics. The findings of the study revealed that SCT was effective in reducing bullying tendencies among primary school pupils as determined by their pre-test and post-test mean scores. Self-control technique had significant efficacy of reducing bullying tendencies on the experimental group. Based on the findings, it was recommended that school Guidance Counsellors should make use of Self-control technique to correct pupils’ bullying behaviour.